Histopathological Spectrum of Thyroid Lesions: A Retrospective Analysis in Albieda Medical Center - El Sharif Khalil; Hanan Mohamed; Khadeejah Abraheem (AlQalam Journal of Medical and Applied Sciences, 2026)
Disorders of the thyroid gland are a major health issue worldwide and represent a common concern in clinical practice. The histopathological diagnosis of different thyroid pathologies is both challenging and essential, as the diagnoses range from non-neoplastic to neoplastic conditions. This study aims to evaluate the histopathological patterns of lesions in thyroidectomy specimens among the population in El-Beyda city/ Libya. Thyroidectomy specimens received in the histopathology laboratory were included in the study. A total of 62 thyroid samples were histopathologically examined. The majority were female, 48 (77.4%), and 14 (22.5%) were males, female to male ratio (3.4:1). The age of the patients ranged from 15 to 78 years, with a mean age of 40 years. The histopathological types of thyroid lesions were 49 (79.0%) non-neoplastic lesions, while the thyroid neoplastic disorders were 13 (21%), of which 8 (12.9%) were benign conditions, including adenoma (both follicular and Hurtle cell type), and 5 cases (8.1 %) were malignant neoplastic lesions. In conclusion, the most prevalent histological variant of thyroid lesion in our study is a non-neoplastic thyroid lesion, with multinodular goitre and Hashimoto’s thyroiditis being the most frequent subtypes. In comparison, neoplastic thyroid disease, although it is less frequent, Follicular adenoma is the most common.